Concept Selection and Translation Strategy: Subtitling for the Deaf based on Corpus Analysis - Jiménez Hurtado, Catalina; Martínez Martínez, Silvia (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
In the past 20 years, corpus analysis has been applied to different translation modalities. This study used an annotated multimodal corpus of 52 international films of different genres, which had been dubbed in Spanish and subtitled for Spanish Deaf and Hard-of-Hearing (DHH) viewers, according to the AENOR, UNE 153010 (2012) standard. The corpus was annotated at two levels. At the first level, we annotated the information that professional subtitlers selected from the audio mode of the source text to translate into subtitles. At the second level, captured information regarding the translation strategies was used. This allowed us to analyse the translation process and reflect the translation preferences of professional subtitlers. Our first objective was to show how corpus analysis can be applied to the study of multimodal texts. The second objective was to provide valuable insights into the understanding, description and specification of the conceptual and epistemological nature of subtitling for the DHH.